2014
DOI: 10.2215/cjn.11001013
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Falls and Risk of Mortality among Older Adults on Chronic Peritoneal Dialysis

Abstract: Background and objectives More than 40% of elderly hemodialysis patients experience one or more accidental falls within a 1-year period. Such falls are associated with higher mortality. The objectives of this study were to assess whether falls are also common in elderly patients established on peritoneal dialysis and evaluate if patients with falls have a higher risk of mortality than patients who do not experience a fall.Design, setting, participants, & measurements Using a prospective cohort study design, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 25 publications
0
24
2
4
Order By: Relevance
“…Falls in the elderly population are associated with increased hospitalization, need for long-term care, and mortality (4,8,12,16,28). Other consequences include fear of falling, resulting in physical activity restriction, functional decline, and frailty (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Falls in the elderly population are associated with increased hospitalization, need for long-term care, and mortality (4,8,12,16,28). Other consequences include fear of falling, resulting in physical activity restriction, functional decline, and frailty (29).…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol has previously been described in detail (8,12). Briefly, all end-stage renal disease patients 65 years and over undergoing chronic dialysis treatment during the period April 9, 2002, to April 9, 2003, at the University Health Network were approached to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, they have a three to four times greater risk for hip fractures compared to the general population 8,9 . The morbidity and mortality are higher in the hemodialysis population 6 and in peritoneal dialysis patients as well 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the incidence of falls in HD patients is about 1.2-1.6 per patient-year, or 0.2-0.37 per patient-year for patients with severe conditions requiring emergency care (20)(21)(22). A recent prospective cohort study showed that the incidence of falls may increase to 1.7 per patient-year for older PD patients (23). To our knowledge, no study has directly compared the risk of falls between PD and HD patients.…”
Section: Discussionmentioning
confidence: 99%